The Effect of Using Preventive Rehabilitation Exercises in Reducing Sports Injuries among Swimmers of Salah Al-Din Sports Club - Mahmood, Ali Qays (Pubmedia Jurnal Pendidikan Olahraga, 2026)
This research sought to assess how effective a prehab program of exercise would be at decreasing the incidence/s of sports-related injury and improving the physical and functional efficiency of swimmers from the Salah Al-Din Sports Club as they attempt to deal with the repeated biomechanical loads that swimming places on their bodies, most importantly on their shoulder joint(s). An experimental methodology was utilized that included a one-group design using purposive sampling of six (6) youth swimmers (16-20 years) to participate in a preventive training program over eight (8) weeks with twenty-four (24) training sessions each involving between sixty (60%) percent and eighty (80%) percent intensity based on their maximum effort. The program consisted of specialized strength exercises using weights, elastic resistance bands, and stretching exercises to develop the strength of stabilizing muscles and to improve the dynamic flexibility of the ligaments and tendons. The statistical analysis showed a significant change between the two assessments of the explosive power of arms. Explosive power of arms measured at 8.34 m increased to 10.05 m. There was a significant improvement for the strength endurance of the (shoulder muscles) shoulder with a statistical significant (0.009) increase. The increase in the speed-strength was minimal again with no statistical significance but confirmed that with physical intervention (hypo, hyper) the subject was able to improve their (hyperbola)(i) the range of motion; (ii) stabilize the humeral head; and ( iii) reduce chronic inflammatory tissue damage to soft tissue due to the chronic cumulative fatigue. It is recommended that each of the described activities be incorporated into the primary components of all training sessions in order to fix movement patterns. This will also help to eliminate harmful compensatory mechanisms and result in effective muscle development that will decrease water resistance and provide sustained athletic performance in the long-term.